COMPARATIVE STUDIES OF THE STRENGTH CHARACTERISTICS OF CONCRETE BLOCKS WITH TITANIUM AND IRON RODS (BARS) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The relevance of the topic of the work was shown by the accident of a multi-storey residential building in Miami, which was caused by corrosion of steel reinforcement in reinforced concrete.There is a need to maintain the bearing capacity of structures for a long time in a humid climate, aggressive environmental influences and temperature fluctuations with a lower consumption of materials used.The use of titanium will allow changing some parameters of titanium concrete structures in comparison with reinforced concrete structures. The protective layer of concrete, which serves to protect the reinforcement from the effects of the external environment, will be significantly reduced. This will help to reduce the mass of concrete structures while maintaining strength properties and will allow you to create lighter structures that can withstand heavy loads.Strength tests were carried out on concrete blocks reinforced with smooth iron or titanium rods Ø10 mm, which showed the prospects of replacing steel reinforcement with titanium reinforcement in reinforced concrete.